2016
DOI: 10.17221/8848-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of human odours to extremely high temperature as revealed by trained dogs

Abstract: Human scent is a complex combination of many chemical substances. Skin is supposed to be one of sources of scent traces. The values of the boiling points of human scent compounds were supposed to be lower than 300°C. The purpose of the study was to determine the temperature at which the human scent is degraded so that a dog would not be able to identify it. In contrast to expectations, eight dogs used in the experiment almost flawlessly identified human scents from five scent donors exposed to temperatures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…This makes the compound easily volatile, more sensitive to the environmental condition and accessible to diminished in a minute or hours (59). In other forms, the low volatile compound is crucial in forensic context as it persists for a more extended period in the surrounding, with steady decay of the compound and low reaction with other compounds (60)(61)(62). This is supported by a previous study, which showed a lower volatile compound recovered a higher amount from the ageing sample than a high and moderate volatile compound.…”
Section: Blood Odourmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes the compound easily volatile, more sensitive to the environmental condition and accessible to diminished in a minute or hours (59). In other forms, the low volatile compound is crucial in forensic context as it persists for a more extended period in the surrounding, with steady decay of the compound and low reaction with other compounds (60)(61)(62). This is supported by a previous study, which showed a lower volatile compound recovered a higher amount from the ageing sample than a high and moderate volatile compound.…”
Section: Blood Odourmentioning
confidence: 99%
“…Several studies have been conducted to determine the level stability of trace odour. Santariová, M. et al (61) experimented on the resistance of the human body odour at different temperature levels using a canine as a detector. The result is enthralling as the canine correctly identified a trace odour even though it had been exposed to high temperatures up until 900 °C.…”
Section: Blood Odourmentioning
confidence: 99%